Epithelial–Mesenchymal Transition Induced by TNF-α Requires NF-κB–Mediated Transcriptional Upregulation of Twist1 - Li, Chia-Wei; Xia, Weiya; Huo, Longfei; Lim, Seung-Oe; Wu, Yun; Hsu, Jennifer L.; Chao, Chi-Hong; Yamaguchi, Hirohito; Yang, Neng-Kai; Ding, Qingqing; Wang, Yan; Lai, Yun-Ju; et al. (Cancer research (Chicago, Ill.), 2012)
Proinflammatory cytokines produced in the tumor microenvironment facilitate tumor development and metastatic progression. In particular, TNF-α promotes cancer invasion and angiogenesis associated with epithelial–mesenchymal transition (EMT); however, the mechanisms underlying its induction of EMT in cancer cells remain unclear. Here we show that EMT and cancer stemness properties induced by chronic treatment with TNF-α are mediated by the upregulation of the transcriptional repressor Twist1. Exposure to TNF-α rapidly induced Twist1 mRNA and protein expression in normal breast epithelial and breast cancer cells. Both IKK-β and NF-κB p65 were required for TNF-α–induced expression of Twist1, suggesting the involvement of canonical NF-κB signaling. In support of this likelihood, we defined a functional NF-κB–binding site in the Twist1 promoter, and overexpression of p65 was sufficient to induce transcriptional upregulation of Twist1 along with EMT in mammary epithelial cells. Conversely, suppressing Twist1 expression abrogated p65-induced cell migration, invasion, EMT, and stemness properties, establishing that Twist1 is required for NF-κB to induce these aggressive phenotypes in breast cancer cells. Taken together, our results establish a signaling axis through which the tumor microenvironment elicits Twist1 expression to promote cancer metastasis. We suggest that targeting NF-κB–mediated Twist1 upregulation may offer an effective a therapeutic strategy for breast cancer treatment. Cancer Res; 72(5); 1290–300. ©2012 AACR.